The Value of Multicultural Education and Tolerance in Indonesian History Learning Textbooks for Senior High School - Samiah, Wardah; Andi, Andi (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study aimed to find out how the presentation of Indonesian history learning textbooks published by Erlangga, Grafindo, and Kemendikbud presented Multicultural and Tolerance texts. This study used a qualitative research method with a library research approach. The primary data source used in this research is Indonesian history textbooks published by Erlangga, Grafindo, and Kemendikbud. The data collection technique used in this study was documentation techniques, and data analysis was carried out using content analysis.his study uses a qualitative technique with the content analysis method of texts relating to multiculturalism and tolerance in books. The results of this study indicate that the three textbooks for students and teachers of Indonesian history for class X in DKI Jakarta present multicultural and tolerant texts on the lives of Indonesian ancestors and are emphasized as the main capital of Indonesian society to progress.